Lebanese Women's Awareness of Polycystic Ovarian Syndrome and Its Complications: A Cross-Sectional Study - Ahmadieh, Hala; Aboudib, Khaled; Khalaf, Iman Al; Dassouki, Weam; Charbaji, Loulwa (Journal of Diabetes and Endocrine Practice, 2022)
Background Polycystic ovarian syndrome (PCOS) is a common disorder in females with many different presentations and potentially life-threatening complications. However, the awareness of females about this disorder tends to be lacking. This study aims to assess the knowledge about PCOS among Lebanese women in the reproductive age group.Methods This cross-sectional study was performed on 421 women aged between 18 and 51 years from all governorates in Lebanon. Participants signed informed consent prior to their participation, and they were selected through convenient sampling. A well-conducted questionnaire was utilized after the Institutional Review Board's Committee approved the study at Beirut Arab University prior to data collection. Data entry was completed with SPSS (IBM version 23.1) and analyzed using mean, standard deviation, percentages, chi-squared test, and p-values.Results Among 421 participants, 75% were aware of PCOS. Around 50% knew about PCOS's various signs and symptoms, whereas only a minority knew about its complications. Furthermore, most participants were aware of the importance of lifestyle modifications in alleviating PCOS symptoms.Conclusion The results of this study show that Lebanese women were aware of common symptoms of PCOS. On the other hand, their knowledge was minimal regarding its more complex manifestations and complications.
Keywords: polycystic ovarian syndrome; complications; life-threatening; awareness; reproductive age group